A COMPARATIVE INTERPRETATION OF HENRY JAMES’S NOVELLA THE FIGURE IN THE CARPET (Journal of Contemporary Philology, 2020)
This paper focuses on the interpretation of Henry James’s novella The Figure in the Carpet (1896) through a series of interpretative models. In the first part of this paper we place the writing of this novella in the context of James’s autobiography and his Notebooks. In the second part we read The Figure in the Carpet, from the author’s view on textual strategy, mainly from the aspect of the construction of the story and the plot (by applying Peter Brooks’s theory of narratology), and also by James’s use of language as a medium for seduction and delay of meaning and sense (with the help of Gilbert Keith Chesterton’s and Tzvetan Todorov’s comments). The novella is read in constant dialogue with James’s remarks from his Notebooksand his Prefaces from The New York Edition of his works. In thethird part we place The Figure in the Carpet in a comparative perspective; firstly, in the context of James’s other works, and secondly, in the context of influences, mainly from French writers, especially from Flaubert. Moreover, some naïve readings are detected, mainly as a counterpoint to our reading of the novella. In the conclusion we position James as a liminal figure functioning as a bridge between the literature of the 19th century and the one of the 20th century.
Keywords: Henry James; literary hermeneutics; comparative literature; plot; story; narratology